Seawater Electrolysis Using All-PGM-Free Catalysts and Cell Components in an Asymmetric Feed - Frisch, Marvin L.; Thanh, Trung Ngo; Arinchtein, Aleks; Hager, Linus; Schmidt, Johannes; Brückner, Sven; Kerres, Jochen; Strasser, Peter (ACS Energy Letters, 2023)
In arid coastal zones, direct seawater electrolysis appears particularly intriguing for green hydrogen production. State-of-the-art direct seawater electrolyzers, however, show unsatisfactory performance and rely on large amounts of platinum-group metals (PGMs) in the electrodes or hidden as transport layer coatings. Herein, we report an asymmetric-feed electrolyzer design, in which all cell components consist of PGM-free materials. Cobalt- and nickel-based phosphides/chalcogenides not only serve as active and robust electrocatalysts but also are put forth as porous transport layer (PTL) surface coatings enhancing selective seawater splitting performance. In a systematic design study at the single-cell level, we report the integration of our catalysts and PTLs into a membrane-electrode assembly (MEA) using a customized, terphenyl-based anion-exchange membrane (AEM). The presented entirely PGM-free electrolyzer achieves industrially relevant current densities of up to 1.0 A cm-2 below 2.0 Vcell in standardized alkaline seawater and dry cathode operation.
CRIS-Team Scopus Importer:2023-06-30